Optimalisasi Proses Pembelajaran Sekolah Melalui Implementasi Sistem E-Learning Berbasis Web Untuk Peningkatan Efektivitas Dan Efisiensi - Brawijaya, Herlambang; Samudi, Samudi; Widodo, Slamet (Journal of Information System, Applied, Management, Accounting and Research, 2024)
in the digital era, education faces challenges in improving the effectiveness and efficiency of the learning process. One proposed solution is the implementation of web-based e-learning systems, which allow for flexibility and interactivity in learning. This study aims to develop a web-based e-learning system using the Extreme Programming (XP) method, an iterative and collaborative software development approach that accommodates changes in user requirements quickly. The research stages include needs analysis, design, development, and system testing, conducted iteratively in accordance with XP principles. The results show that the developed e-learning system enhances learning effectiveness by providing more structured, interactive access to learning materials and facilitating better communication between teachers and students. Additionally, efficiency is achieved by reducing operational costs and the time required for distributing materials and assignments. System testing indicates a high level of user satisfaction in terms of both functionality and ease of use. This study contributes to the optimization of the learning process through the implementation of information technology in education.